1999
DOI: 10.1021/ja981683+
|View full text |Cite
|
Sign up to set email alerts
|

How Does Alcohol Dissolve the Complex of DNA with a Cationic Surfactant?

Abstract: The single-chain observation of isolated giant DNAs complexed with a cationic surfactant, CTAB, was performed using fluorescence microscopy. The DNA−CTAB complex exhibits a re-entrant transition, collapsed globule → elongated coil → collapsed globule, with an increase in the alcohol concentration. The existence of DNA in its coil state at an intermediate concentration of alcohol implies that this environment is a good solvent for the DNA chains. On the other hand, the presence of the globule state at both low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
64
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 25 publications
7
64
0
1
Order By: Relevance
“…21,22 Sergeyev et al have found that double stranded DNA molecules, when combined with the cationic surfactant molecule, cetyltrimethylammonium bromide (CTAB), displayed entrant and reentrant coil-globule transitions in aqueous ethanol solution as a function of the concentration of ethanol. 20 This finding confirmed that the DNA-surfactant complex, DNA-CTA, in pure ethanol was in the globular state even in a condensed solution. DNA-CTA globules are considered stable in ethanol solution because of the encapsulated structure of DNA by surfactant CTA 1 molecules.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…21,22 Sergeyev et al have found that double stranded DNA molecules, when combined with the cationic surfactant molecule, cetyltrimethylammonium bromide (CTAB), displayed entrant and reentrant coil-globule transitions in aqueous ethanol solution as a function of the concentration of ethanol. 20 This finding confirmed that the DNA-surfactant complex, DNA-CTA, in pure ethanol was in the globular state even in a condensed solution. DNA-CTA globules are considered stable in ethanol solution because of the encapsulated structure of DNA by surfactant CTA 1 molecules.…”
supporting
confidence: 64%
“…DNA-CTA globules are considered stable in ethanol solution because of the encapsulated structure of DNA by surfactant CTA 1 molecules. 20,23 This stable globular complex suggests the possibility of making a globular solid without constructing chain entanglements among molecules.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…[24][25][26][27] Therefore, the vesicles in Figures 4D and 4G are much bigger than those in Figures 2C and 2D.…”
Section: Resultsmentioning
confidence: 86%
“…This interaction leads to the neutralization of charge on the phosphate group and induces a high degree of hydrophobicity that in turn brings down the solubility of the DNA -CTAB complex (Kunjappu and Nair, 1992). Since DNA-surfactant complexes are generally insoluble in water (Sergeyev et al, 1999), the difficulty in solubilizing the DNA pellets after CTAB precipitation is one of the drawbacks observed in the process exploiting DNA-CTAB complex formation for isolation of plasmid DNA from lysate of bacterial culture (Ishaqu et al, 1990;Lander et al, 2002).…”
Section: Resultsmentioning
confidence: 99%